Activation of Aspen Wood with Carbon Dioxide and Phosphoric Acid for Removal of Total Organic Carbon from Oil Sands Produced Water: Increasing the Yield with Bio-Oil Recycling - Hill, Josephine M. (2016)
Several samples of activated carbon were prepared by physical (CO2) and chemical (H3PO4) activation of aspen wood and tested for the adsorption of organic compounds from water generated during the recovery of bitumen using steam assisted gravity drainage. Total organic carbon removal by the carbon samples increased proportionally with total pore volume as determined from N2 adsorption isotherms at −196 °C. The activated carbon produced by CO2 activation had similar removal levels for total organic carbon from the water (up to 70%) to those samples activated with H3PO4, but lower yields, due to losses during pyrolysis and activation. A method to increase the yield when using CO2 activation was proposed and consisted of recycling bio-oil produced from previous runs to the aspen wood feed, followed by either KOH addition (0.48%) or air pretreatment (220 °C for 3 h) before pyrolysis and activation. By recycling the bio-oil, the yield of CO2 activated carbon (after air pretreatment of the mixture) was increased by a factor of 1.3. Due to the higher carbon yield, the corresponding total organic carbon removal, per mass of wood feed, increased by a factor of 1.2 thus improving the overall process efficiency.